"It's My Time": Older Adults' Experiences and Perceived Benefits of Participation in an Intergenerational Rock Band. Issue 2 (25th November 2019) - Wlodarczyk, Natalie
Abstract: The purpose of this qualitative content analysis was to explore the experiences and perceived benefits for older adult members who participated in an intergenerational rock band (IGRB) pairing older adults with college students. Participants ( n = 29) were first-time older adult IGRB members who completed semi-structured interviews over the course of 5 years. Interviews were completed within 1 week of the conclusion of the semester-long participation in the IGRB. Each interview was digitally recorded, manually transcribed, and analyzed using an iterative approach to thematic analysis. Experiences and perceived benefits associated with participation in the IGRB for these older adults were encompassed by four themes: Staying Active, Wanting to Try Something New, Feeling Connected, and Seeking Positive Experiences. Findings indicate that an IGRB is an innovative, collaborative, and inclusive intergenerational music-making experience that leaves a multifaceted and overall positive impact on its older adult members. Themes suggest that older adults with musical backgrounds may enjoy an experience like an IGRB because it brings a level of familiarity coupled with the opportunity to try something new and different from their previous experiences with music. A key contribution of this study is the importance of promoting a judgment-free environment for singing that is inclusive of all ability levels. Developing a better understanding of older adults' motivations for participating in an IGRB may help us to plan future music experiences for older adults and broaden our reach to the older adult community.